1997
DOI: 10.1093/hmg/6.6.953
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Wide Search for Susceptibility Loci in Three European Malignant Hyperthermia Pedigrees

Abstract: Malignant hyperthermia (MH) is an autosomal dominant disorder which is potentially lethal in susceptible individuals on exposure to commonly used inhalational anaesthetics and depolarising muscle relaxants. Crises reflect the consequences of disturbed skeletal muscle calcium homeostasis. Susceptibility was first localised to chromosome 19q13.1 and the skeletal muscle ryanodine receptor, RYR1 (the calcium release channel of the sarcoplasmic reticulum). Defects in this gene have been identified which cosegregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Demonstrated defects of the sodium channel a-subunit protein leading to myotonia fluctuans, can also be associated with abnormal responses to succinylcholine, including muscle rigidity [50,51]. Extensive searches have been carried out to identify other MH loci [52].…”
Section: T H E M O L E C U L a R B A S I S F O R M A L I G N A N T H mentioning
confidence: 99%
“…Demonstrated defects of the sodium channel a-subunit protein leading to myotonia fluctuans, can also be associated with abnormal responses to succinylcholine, including muscle rigidity [50,51]. Extensive searches have been carried out to identify other MH loci [52].…”
Section: T H E M O L E C U L a R B A S I S F O R M A L I G N A N T H mentioning
confidence: 99%
“…Molecular genetic studies have mapped the primary locus of MH to chromosome 19q 13.1, to the gene encoding the ryanodine receptor calcium channel (RYR1; MIM# 180901) (MacLennan et al 1990;McCarthy et al 1990). Linkage studies however, have revealed MH as a heterogenetic disease (Levitt et al 1991;Deufel et al 1992;Monnier et al 1997;Robinson et al 1997); in fact mutation screenings have so far identified 23 distinct mutations in the RYR1 and approximately 50% of MH families are estimated to have mutations in the RYR1 gene (McCarthy et al 1990;MacLennan and Phillips 1992;Robinson et al 1997;Manning et al 1998b;Jurkat-Rott et al 2000;McCarthy et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…29 A systematic linkage study using a set of polymorphic microsatellite markers covering the entire human genome in a small number of large, apparently non-chromosome 19 linked European MH families, identified a locus on chromosome 3q13.1 (MHS4), 70 a locus on chromosome 1q (MHS5), 50 59 and a tentative locus on chromosome 5q (MHS6). 59 A causative gene at the MHS3 and MHS4 locus has yet to be identified. The CACNL1A3 gene encodes the a1-subunit of the DHP receptor maps to the MHS5 locus and functions as a voltage gated channel.…”
Section: Ryanodine Receptor (Ryr1)mentioning
confidence: 99%